Current research in Egyptology 2021 : proceedings of the Twenty-First Annual Symposium, University of the Aegean, 9-16 May 2021 - Apostola, Electra,; Kekes, Christos, (Access archaeology., 2022)
15 Egyptological and Papyrological papers investigate a great variety of issues, including social and religious aspects of life in ancient Egypt, ritual and magic, language and literature, ideology of death, demonology, the iconographical tradition, and intercultural relations, ranging chronologically from the Prehistoric to the Coptic period.